Study of Proximate Composition of Some Wild and Farmed Labeo rohita and Cirrhinus mrigala Fishes - Hadyait, Muhammad Arfan; Ali, Asif; Bhatti, Ehsan Mahmood; Qayyum, Aroosa; Ullah, Muhammad Zafar (PSM Biological Research, 2018)
The proximate composition of farmed and wild Labeo rohita and Cirrhinus mrigala was determined to identify nutritional differences due to habitat change. Thirty (30) fishes in total from wild and farm raised population of size group (700-1000 gm) were collected from Head Qadirabad River Chenab, Head Rasul River Jehulm and Army Fish Farm, Lahore. Fish samples were analyzed for protein, fat, moisture and ash. The chemical composition of two fish species collected from different sources was compared and the difference was observed. Elevated levels of protein and low fat contents were observed in the farmed fishes. The moisture and ash contents were higher in both wild and farmed fishes, respectively. It is concluded the farmed fish is nutritionally better than wild irrespective of the species.